CRITICAL ANALYSIS OF PHYSIOTHERAPY AND REHABILITATION SERVICES IN COORDINATED CARE PLANNING AND REHABILITATION STRATEGIES FOR IMPROVED PATIENT MOBILITY AND FUNCTIONALITY - 1Mohammed Saeed Saleh Alwadai, 2Yazeed Saleh Mohamad Almwalad, 3Hadi Hassan Ali alduways, 4Samar Saleh Abdu Bahkali, 5Ali Yahya Hussein Ozran, 6Naif Hadi Yahya Musarrihi, 7Hussein Yahya Hussein ozran,,; 8Mesfer Mahde Ali Lasloom, 9Jaber Saleh Askar Lsloom, 10Hamad Saleh Askar Lsloom, 11Ibrahim Abdullah M Shabaani, 12Saad Eissa Ali Madkhali, 13Jaber saeed ali Alsallum, (Chelonian Research Foundation, 2023)
Physiotherapy and rehabilitation services stand as indispensable pillars in the quest to enhance patient mobility and functionality, particularly within the realm of coordinated care planning .This article gives a basic assessment of their viability in progressing and patient results. Through a cautious survey of the existing writing, an efficient survey, and a comprehensive dialogue of the results, this study gives a better understanding of the issues, completed activities, and proposals concerning Physiotherapy and rehabilitation in a care office. The findings highlight the significance of combining distinctive medicines, from exercise to manual therapy, while empowering collaboration between specialists. This combination benefits all-encompassing treatment and progresses the patient's mobility, ability to work, and overall quality of life. In expansion, this audit highlights the need to address imbalances in these administrations and advocates for an efficient approach to ensure that care is given evenhandedly over diverse patient groups. By implementing these suggestions and creating a collaborative healthcare framework, specialists can unlock the complete potential of physiotherapy and rehabilitation, empowering patients to realize great things and empowering development and work. Keywords: physiotherapy, rehabilitation, Coordinated Care Planning, patient mobility, functionality